The Influence of Brand Image And Price Perception On Purchase Decisions - Umbola, Fitriana; Mawuntu, Priska; Potolau, Michel (Jurnal Entrepreneur dan Entrepreneurship, 2019)
The success of a company is inseparable from the ability of the marketing department to help companies to know the extent to which both the brand and price are well known and perceived by the public. This study aims to examine the influence of brand image and price perception on purchase decisions. The sample size is 87 buyer of motorcycle. Data was analysed by using multiple regression. The result shows that there is an influence of brand image and price perception on the purchase decision.